2016
DOI: 10.4314/ovj.v6i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple endocrine neoplasia similar to human subtype 2A in a dog: Medullary thyroid carcinoma, bilateral pheochromocytoma and parathyroid adenoma

Abstract: Human multiple endocrine neoplasia subtype 2A (MEN 2A) is characterized by medullary thyroid carcinoma, pheochromocytoma and parathyroid hyperplasia or adenoma in the same individual. In this report, a case of a female Rottweiler with medullary thyroid carcinoma, bilateral pheochromocytoma and parathyroid adenoma was described. Clinical manifestations of muscle weakness, polydipsia, polyuria, diarrhea and weight loss were observed. Two adrenal neoplasms were identified incidentally by ultrasonography, and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…As previously described in other case reports on dogs with MEN type 2‐like syndrome, the thyroid function of the dog from this study appeared preserved 5, 14 . Nevertheless, the presence of euthyroid sick syndrome may mask increased serum TT4 concentrations and was not investigated in our study.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…As previously described in other case reports on dogs with MEN type 2‐like syndrome, the thyroid function of the dog from this study appeared preserved 5, 14 . Nevertheless, the presence of euthyroid sick syndrome may mask increased serum TT4 concentrations and was not investigated in our study.…”
Section: Discussionsupporting
confidence: 51%
“…More specifically, MEN type 2 is caused by a dominant autosomal mutation within the RET proto‐oncogene 19, 20 . This mutation has also been described in one dog with MEN type 2‐like syndrome and likely occurred in two other dogs with MEN‐like syndromes based on the phenotypic expression of this neoplastic entity 5, 7, 14 . Moreover, familial MTC has been reported in four Alaskan Malamutes, further suggesting a hereditary predisposition for this syndrome in dogs 21 …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In both subtypes it is associated with medullary thyroid carcinoma, and subtype 2A also presents hyperplasia or parathyroid adenoma (PA). Although in the dog PCC is usually sporadic (single neoplasm), it has also been reported in the same neoplastic association as that present in the MEN 2A syndrome in two dogs (Peterson et al, 1982;Soler Arias et al, 2016). A case of PCC in association with PA without medullary thyroid carcinoma in a 15-year old Yorkshire terrier was reported by Wright et al (1995).…”
Section: Introductionmentioning
confidence: 95%
“…Soler Arias et al Open Veterinary Journal, (2017), Vol. 7(4): 332-336 ________________________________________________________________________________________________________ This case, like the one reported by Wright et al (1995), shares strong similarities with MEN 2A syndrome, but the neoplastic association could not be included in that classification due to the absence of medullary thyroid carcinoma, which in humans shows a 100% penetrance (Peterson et al, 1982;Wright et al, 1995;Soler Arias et al, 2016). On the other hand, in PCC and PAI report included in human literature, no association was found that could explain the concurrence of both entities (García et al, 2008).…”
Section: Introductionmentioning
confidence: 99%